Persistence of Individual Unemployment in Indonesia: Dynamic Probit Analysis from Panel SUSENAS 2008-2010 - Pasaribu, Syamsul Hidayat (International Journal of Economics and Financial Issues, 2016)
This paper presents a dynamic probit analysis of individual unemployment incidence using a panel survey on the National Socio-Economy (SUSENAS), 2008-2010. It compares a variety of dynamic random effects estimators, particularly focusing on the Heckman's (1981) and Wooldridge's (2005) approaches. The main result shows a strong evidence of persistence or state dependence of individual unemployment in Indonesia and therefore consistent with the theory of scar unemployment. This means that a person's unemployment experience has an implication to his/her future of labour market experience. Keywords: persistent unemployment; state dependence; Heckman's estimator; Wooldridge's estimator JEL Classifications: J64, J65, J68